Self-Efficacy and High-Order Thinking Skills (HOTS) In Mathematics: A Systematic Literature Review - Marlina; Baist, Abdul; Nopitasari, Dian (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2026)
The study aims to examine the influence of self-efficacy on high-order thinking skills in mathematics learning while identifying the factors underlying the observed differences in outcomes. The method used is a Systematic Literature Review. Fifteen articles published between 2020 and 2025 were selected as the research subjects. Data were collected from four databases, Scopus, ERIC, ScienceDirect, and Google Scholar, using the primary keywords “self-efficacy” and “HOTS”. The journals were systematically reviewed and analyzed following the PRISMA 2020 guidelines. The results of the study indicate that self-efficacy positively affects high-order thinking skills in mathematics among secondary school students. Students with high self-efficacy generally demonstrate stronger abilities in analysis, evaluation, problem-solving, and creative thinking than students with low self-efficacy. However, for the problem-solving indicator, 7% of the results showed no significant relationship. The variation in results is attributed to learning strategies that do not support the development of students' understanding of mathematical concepts. Therefore, teachers are advised to implement learning strategies that can enhance students’ self-efficacy to support the development of HOTS.